Pengaruh Kinerja Keuangan, Good Corporate Governance (Gcg), Dan Leverage Terhadap Nilai Perusahaan (Studi Kasus Pada Perusahaan Bumn Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2018) - Indah Handayani; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThe purpose of this study is to find out how the influence of good corporate governance proxied by the board of commissioners on company value, financial performance that is proxied by ROE and leverage proxied by DER. This survey is a kind of quantitative survey. The population included in this study is state-owned enterprises listed on the Indonesian Stock Exchange (IDX) during this period 2016-2018. The samples were selected using purposeful sampling. The results showed that good corporate governance Financial performance has a positive and not significant effect on firm value. While leverage has a significant positive effect on firm value.Keywords: Financial Performance, Good Corporate Governance, Leverage and Company Value.